Pattern of ophthalmic referral from primary healthcare centres to secondary and tertiary hospitals in Qassim Province, Saudi Arabia - AlHarkan, Dora Hamad; Altowayan, Rawan Mohammed A.; Alharbi, Amjad Mohammed; Aljumaiah, Sahar Mohammed; Alhijji, Lamia Ibrahim; Alkhezzy, Buthaina Suliaman B. (International Surgery Journal, 2020)
Background: References of patients with ocular diseases are an indirect indicator that reflects integration of primary eye care into primary health care system. The study reviewed the ophthalmic references from four randomly selected primary health care centres to ophthalmic unit of secondary and tertiary hospitals in Qassim Province of Saudi Arabia. Methods: This was a retrospective health record review study was undertaken at four PHC centres in Qassim region during the year 2017. All cases referred for eye care from January 2015 until December 2016 were included. Prevalence of ophthalmic reference, profile of ophthalmic patients and ophthalmic diagnosis were analysed. Results: From primary health care centres, 423 eye cases from 1,387,996 population of catchment area were referred. The annual prevalence of eye reference was 1.5 per 10,000. Vision screening and diabetic retinopathy evaluation comprised of 55.5% of total reference. Conclusions: Poor reference pattern from primary health care centers to secondary and tertiary eye centre suggest urgent and strong need of implementing primary eye care in the primary health care centres of Saudi Arabia. Referral of simple eye cases are increasing the workload of ophthalmologists and can delay urgent referrals like cases of diabetic retinopathy screening.